Pelatihan Digital Marketing Pada Asosiasi Umkm Profesional Dan Manajemen Indonesia - Bunga Aditi; Olga Theolina Sitorus; Taufiq Risal (LPPM STIKOM Tunas Bangsa, 2022)
Members of the Indonesian Professional and Management MSME Association do not understand the implementation of digital marketing, while the current situation is that many people are using digital marketing in the business of selling, purchasing, marketing products and others, if they do not understand and follow the development of this technology, they will experience problems. left behind in the world of technology. The Community Service Team as PKM implementers assisted by lecturers and students as a solution in increasing the ability to provide training on digital marketing to partners. The purpose of this service activity is to provide knowledge about digital marketing. The method of implementing activities used is in the form of training, interactive discussion with all training participants. This activity uses knowledge in theory and practice in the room. This training provides an assessment to the participants through a written test using a pretest and posttest with 20 participants participating. The results of the final assessment of the activity, that the participants were able to understand the material well based on the results of the assessment scores from the posttest results, with an average value of 92.